Building on the Huntington Library's literary foundation. Issue 1 (November 2018) - Hodson, Sara S.
Abstract : The Huntington Library, Art Collections and Botanical Gardens was founded in 1919 by Henry E. Huntington, a real estate and railroad businessman. In the research library, Huntington collected rare material relating to his own heritage as an Anglo-American. Often purchasing entire private libraries of rare books and manuscripts, he amassed in a short span of years a magnificent collection, including such literary treasures as Shelley's notebooks, and seven drafts of Thoreau's Walden . Huntington also bought individual items and small groups of material, such as the first instalment of Jack London's Papers. Following his death in 1927, library staff continued to acquire literary treasures and research material that would build on and augment the rich collections in the library. Over the decades, the library gathered the papers of such writers as Wallace Stevens, Kingsley Amis, Elizabeth Jane Howard, Patrick Kinross, Christopher Isherwood, Hilary Mantel, Charles Bukowski, Octavia E. Butler, Evelyn Waugh and Paul Theroux, ensuring that the library will continue to be a focal point for scholarly researchers and public visitors alike.